Study on the Influence of Brand Positioning on the Competitive Performance of Organizations - Mourad, Aimãn Ibrahim; Serralvo, Francisco Antonio (Future Studies Research Journal: Trends and Strategies, 2018)
Having a differentiated positioning is essential for a organization to survive in some highly competitive, and fast in terms of technology and globalized markets. The positioning is considered one of the key elements in modern marketing management, however, the term positioning has introduced some confusion between marketing and academic professionals. Using mind share and market share as measurable variables of brand positioning and competitive performance, respectively, this study sought to identify the main objective when the brand positioning can influence the competitive performance of an organization. To this end, a quantitative approach was used on a longitudinal desk research and applied to the Spearman correlation technique. It was not possible to identify if the brand positioning is determinant on competitive performance, however, it was concluded that this exerts a moderate influence on the organization’s competitive performance, since the analyzed period showed a moderate positive correlation between the variables, indicating they moves in in the same direction and that the greater the growth of a variable, the larger the probability of occurring the same with each other, contributing to earlier studies. This study also corroborates the definition and distinction in relation to the concepts of brand positioning and competitive positioning, besides to proposing the use of identity as a leading element for the brand positioning strategy.